1998
DOI: 10.1177/03635465980260011001
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Bone Bruises

Abstract: We conducted a prospective study to evaluate bone bruises, or trabecular microfractures, associated with isolated medial collateral ligament injuries. Magnetic resonance imaging was performed on 65 patients with isolated medial collateral ligament injuries determined by physical examination and imaging studies. Of these 65 patients, 29 (45%) had associated trabecular microfractures. Follow-up images were completed at various intervals on 24 of these 29 patients (83%). Complete resolution of these lesions was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(47 citation statements)
references
References 12 publications
1
45
0
1
Order By: Relevance
“…While BML to isolated MCL tear may spontaneously heal in two to four months, it has been reported that BML in a complex knee injury with ACL tear has a slower resolution. 9 Moreover, BML in ACL lesion is predominantly present at three years follow-up when associated with a disruption or a depression of the normal contour of the femoral cortical surface, while lesions without cortical involvement tend to resolve spontaneously in 95% of cases. 10 In addition, the location of the lesion may affect the evolution of BML.…”
Section: Traumatic Bmlmentioning
confidence: 99%
“…While BML to isolated MCL tear may spontaneously heal in two to four months, it has been reported that BML in a complex knee injury with ACL tear has a slower resolution. 9 Moreover, BML in ACL lesion is predominantly present at three years follow-up when associated with a disruption or a depression of the normal contour of the femoral cortical surface, while lesions without cortical involvement tend to resolve spontaneously in 95% of cases. 10 In addition, the location of the lesion may affect the evolution of BML.…”
Section: Traumatic Bmlmentioning
confidence: 99%
“…Miller et al have reported the prevalence of bone bruises in the lateral femoral condyle or lateral tibial plateau to be 45% in acute isolated MCL injuries. 15 …”
Section: Imagingmentioning
confidence: 99%
“…MRI is the best recognized modality for its ability to detect bone bruises after trauma, which is considered to represent a combination of trabecular microfracture, edema, and hemorrhage [12, 13]. The usefulness of MRI in diagnosing spinal fractures has been discussed in previous reports.…”
Section: Discussionmentioning
confidence: 99%